A statistical approach for the fabrication of adaptive pleated fiber reinforced plastics. (1st January 2019) - Ashir, Moniruddoza; Hindahl, Jan; Nocke, Andreas; Cherif, Chokri
Abstract: The increasing demand for fiber reinforced plastics for different high-tech lightweight applications requires their continuous development, for example, by means of high functional density. Among various smart materials, fiber reinforced plastics can be functionalized by actuator materials, in particular shape memory alloys. This paper presents a statistical approach to the fabrication of adaptive pleated fiber reinforced plastics. Three geometrical factors – pleat thickness, pleat height and the spacing between two pleats were identified by the half-normal probability plot that affect the deformation of adaptive pleated fiber reinforced plastics during the activation of shape memory alloys. Overall, four responses were evaluated by means of the design of experiment. Significant statistical models were found for the deformation, level loss per cycle, heating and cooling speed of adaptive pleated fiber reinforced plastics. These statistical models were validated through experimental data by the goodness of fit function. The results of the statistical model tended to fit experimental results.